Role of Student Ratings of Lecturers in Enhancing teaching at Higher Education Institutions: A case study of the Durban University of Technology - Dorasamy, N. (Journal of Economics and Behavioral Studies, 2013)
Evaluation of the quality of programmes by students is considered an important assessment instrument in determining programme effectiveness within higher education institutions. Student ratings of lecturers are only a partial assessment of programmes, since other evaluations beyond students’ perceptions are also considered important within higher education institutions. Student ratings are not only important in determining how students perceive their programmes within a highly competitive higher education landscape in South Africa, but also highlight the strengths and weaknesses of programmes which can be used as an impetus for programme enhancement, especially in view of the increasing number of students entering higher education, while government spending is steadily diminishing. The purpose of this study is to assess student ratings of teaching competencies that can be used for programme evaluation. A quantitative approach was used to analyse the various elements within specific domains in the lecturer evaluation instrument used by the Faculty of Management Sciences at the Durban University of Technology (DUT). The data reported are suggestive of the usefulness of identifying student ratings of important teaching competencies, which is considered as important in a growing student centred orientation within higher education institutions. The article offers constructive analysis of student ratings of various teaching competencies across departments in the faculty, while highlighting strategies to ensure enhanced validity of student ratings. Student ratings of lecturers provide valuable information for faculty to use in programme assessment and consequent programme enhancement. Further, student ratings of lecturers encourages a student’s voice through confidential participation, thereby ensuring that the student experience is fore grounded at the learning and teaching interface.